ORGANIZATION OF DIALOGICAL INTERACTION AS OPTIMAL CONDITION PERSONAL AND DEVELOPMENTAL EDUCATION (Pedagogy of Higher and Secondary Education, 2022)
In this article organizing o f training the dialogue interaction o f pedagogical universities’ students is considered. One of the effective forms o f the training that develops readiness to the interaction and communicative competence is “workshop”.